Colloidal InSb Quantum Dots for 1500 nm SWIR Photodetector with Antioxidation of Surface - Seo, Haewoon; Eun, Hyeong Ju; Lee, Ah Yeong; Lee, Hang Ken; Kim, Jong H.; Kim, Sang Wook (Advanced Science, 2024)
III-V quantum dots (QDs) have emerged as significant alternatives to Cd- and Pb-based QDs, garnering notable attention over the past two decades. However, the understanding of III-V QDs, particularly in the short wave-infrared (SWIR) region, remains limited. InAs QDs are widely recognized as the most prominent SWIR QDs, but their absorption beyond 1400 nm presents various challenges. Consequently, InSb QDs with relatively narrower bandgaps have been investigated; however, research on their device applications is lacking. In this study, InSb QDs are synthesized with absorption ranging from 1000 to 1700 nm by introducing Cl− ions to enhance QD surface stability during synthesis. Additionally, it coated InAs and ZnSe shells onto the InSb QDs to validate photoluminescence in the SWIR region and improve photostability. Subsequently, these QDs are employed in the fabrication of photodetector devices, resulting in photodetection above 1500 nm using Pb-free QDs. The photodetection device exhibited an external quantum efficiency (EQE) of 11.4% at 1370 nm and 6.3% at 1520 nm for InSb core QDs, and 4.6% at 1520 nm for InSb/InAs core/shell QDs, marking the successful implementation of such a device. In detail, the 1520 nm for InSb core device showed a dark current density(JD) value of: 1.46 × 10−9 A/cm2, responsivity(R): 0.078 A/W, and specific detectivity based on the shot noise(Dsh*): 3.6 × 1012 Jones at 0 V.
Keywords: Anti-oxidation; III-V quantum dots; InAs quantum dots; Indium antimony quantum dot; Infrared photodetector; InSb quantum dot; Photo detection; Short wave infrared; Short wave infrared regions; Short wave-infrared photodetector; III-V quantum dots; Indium antimony quantum dots; Short wave-infrared (SWIR) photodetector